What is a worldview? A historical and critical analysis - Elena Paola Carola Alessiato (Danish Institute for International Studies (DIIS), 2022)
The word 'worldview' comes from German philosophy and literally signifies an all-inclusive 'vision of the world'. Nowadays, the word has a more generic cultural or geopolitical usage, often associated with an equivocal or indefinite meaning. Looking at its history, this paper intends to clarify the meaning and implications of the term. For such an analysis, two thinkers, Wilhelm Dilthey and Karl Jaspers, both of whom thematised the concept of Weltanschauung at the beginning of the 20th century, will be taken into account. What follows is a brief depiction of some peculiar and constitutive traits of the concept: the composite nature of it; the connection to life; and the both total and personal value of a worldview for the holder of it. This paper suggests that the potential conflictuality between contrary or competing worldviews is not accidental; rather, it is an aspect of such a conceptual constitution, at whose core is a delicate balance between internal strength and external challenge. This is what the paper calls 'the vitality paradox' of a worldview.
Keywords: 330